2003
DOI: 10.1007/s00425-002-0878-2
|View full text |Cite
|
Sign up to set email alerts
|

Rapid increase of vacuolar volume in response to salt stress

Abstract: Suspension-cultured cells of mangrove [Bruguiera sexangula (Lour.) Poir.] showed a rapid increase in vacuolar volume under salt stress, although there was no change in the cell volume. The rapid increase in the vacuolar volume was an active process, which followed the activation of the tonoplast H + -ATPase and the vacuolar acid phosphatase. The same phenomenon was observed in barley (Hordeum vulgare L. cv. Doriru) root meristematic cells under salt stress but not in pea (Pisum sativum L.). Increases in vacuol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(37 citation statements)
references
References 28 publications
2
34
0
1
Order By: Relevance
“…We can consider the rapid increase in vacuolar Na levels as a mechanism to allow this halophyte to acclimate to a rise in external concentration. Mimura et al (2003) observed the same phenomenon in the cells of the mangrove (Bruguiera sexangula) soon after salt treatment (150 mM NaCl, for 24 h). Our results also suggest that C. maritima has already a basal Na + /H + antiporter activity catalyzing the exchange of Na + for H + across the tonoplast membranes that would result in removal of Na + from cytoplasm into vacuole.…”
Section: Discussionsupporting
confidence: 55%
“…We can consider the rapid increase in vacuolar Na levels as a mechanism to allow this halophyte to acclimate to a rise in external concentration. Mimura et al (2003) observed the same phenomenon in the cells of the mangrove (Bruguiera sexangula) soon after salt treatment (150 mM NaCl, for 24 h). Our results also suggest that C. maritima has already a basal Na + /H + antiporter activity catalyzing the exchange of Na + for H + across the tonoplast membranes that would result in removal of Na + from cytoplasm into vacuole.…”
Section: Discussionsupporting
confidence: 55%
“…In tolerant salt includes such as mangroves and barley, a rapid increase in vacuolar volume in response to salt stress was observed. This phenomenon was not reported in sensitive species such as peas and tomatoes (Mimura et al, 2003). …”
Section: Discussionmentioning
confidence: 86%
“…In order to defend salt-induced oxidative damage, plants are equipped with oxygen radical detoxifying enzymes such as superoxide dismutase, peroxidase and catalase [6], [24]. Accumulation of inorganic ions in vacuoles is common pattern observed in mangrove plants under saline conditions [25], [26], which serves not only to increase cellular osmolarity to counter osmotic stress but also to avoid increases in ionic strength of the cytoplasm [21], [27]. However, previous studies on this topic mostly focused on a certain growth stage of mangroves, how salinity influences mangroves in a dynamic developmental process is not well known.…”
Section: Introductionmentioning
confidence: 99%